Characterization of Sulfur in Raw and Anaerobically Digested Municipal Wastewater Treatment Sludges. (1st February 2013) - Du, Weiwei; Parker, Wayne
Abstract : A microwave‐enhanced acid digestion method that was integrated with inductively coupled plasma‐atomic emission spectrometry was developed and validated for determining total, soluble, and precipitated sulfur in wastewater treatment sludges. The coefficient of variation of this method was less than 4.0%. The recovery of dosed sulfur from sludge samples was between 97.1% and 100.5%. The composition of sulfur in primary and waste‐activated sludge (WAS) before and after anaerobic digestion at 35 and 55 °C was characterized by employing this developed method. There was not an apparent relationship between the precipitated sulfur and nonsoluble iron concentrations in sludges. Raw WAS had a more consistent organic sulfur fractionation because of its relatively homogeneous composition. The organic‐sulfur‐containing components (proteins) of WAS had reduced degradability as compared with that in primary sludge during anaerobic digestion. Digestion at 55 °C increased solubilization but not ultimate conversion of organic sulfur in sludge.